PENGARUH MEDIA PERMAINAN BOWLING KATA TERHADAP KEMAMPUAN LITERASI DINI PADA ANAK USIA 5-6 TAHUN DI TK TUNAS HARAPAN GBKP PEKANBARU - Riris Febrina Sitorus; Devi Risma; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is based on a low of interest in reading and writing (early literacy) in children. Early literacy skills are early reading and writing skills in children. One way to stimulated early literacy skills is with the media game, an example of the game media is word bowling game media. This research is purposed for to know the influence of word bowling games media toward early literation capability of kids 5 to 6 years old in TK Tunas Harapan GBKP Pekanbaru. This research is an experimental study using the design of one group design with pretest and posttest through an observation sheet on early childhood literacy abilities. The sample used in this study was 15 children aged 5-6 years totaling 15 children. File accumulation’s technique that used is observation. Data analysis techniques use the Wilcoxson test using the IBM SPSS Statistics Data 21 Program. Based on the calculation of the Wilcoxson test it is known that Asymp.Sig (2-tailed) is worth 0,000, because the value is smaller than <0,05, it can concluded that “Ha is accepted”. Meaning that there are in early literacy skills for the pretest and posttest. Based on calculation using the Gain formula that is equal to 40.43% in the medium catgory and 59,57% is influenced by other factors, it can be concluded that there is the effect of the word bowling game media on the early literacy skills of children aged 5-6 years at TK Tunas Harapan GBKP Pekanbaru.Key Word: Emergent Literacy Ability, Word Bowling Game Media.